1997
DOI: 10.2105/ajph.87.12.2035
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors for individuals' Lyme disease prevention practices: Connecticut, Maine, and Montana.

Abstract: OBJECTIVES: This study examined factors that predispose individuals to protect against Lyme disease. METHODS: Knowledge, attitude, and practice questions concerning Lyme disease prevention were included in the Behavioral Risk Factor Surveillance surveys in Connecticut, Maine, and Montana. A total of 4246 persons were interviewed. RESULTS: Perceived risk of acquiring Lyme disease, knowing anyone with Lyme disease, knowledge about Lyme disease, and believing Lyme disease to be a common problem were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 25 publications
7
40
1
Order By: Relevance
“…In 1992, Herrington et al (6) found that self-perceived risk of acquiring LD and knowledge about the disease correlated with the use of personal protective measures; however, even in highly LD-endemic areas such as Connecticut, adherence to these personal protective measures varied greatly-only 79% of respondents routinely used tick repellents and 93% reported inspecting themselves for and removing ticks after being outdoors. In 2001, Phillips et al found that 80% of the surveyed residents of Nantucket reported checking their bodies for ticks after potential tick exposures, 53% used protective clothing (such as wearing long pants and long-sleeved shirts), 34% reported routinely avoiding tick infested areas, and 11% reported routine use of tick repellents (7).…”
mentioning
confidence: 99%
“…In 1992, Herrington et al (6) found that self-perceived risk of acquiring LD and knowledge about the disease correlated with the use of personal protective measures; however, even in highly LD-endemic areas such as Connecticut, adherence to these personal protective measures varied greatly-only 79% of respondents routinely used tick repellents and 93% reported inspecting themselves for and removing ticks after being outdoors. In 2001, Phillips et al found that 80% of the surveyed residents of Nantucket reported checking their bodies for ticks after potential tick exposures, 53% used protective clothing (such as wearing long pants and long-sleeved shirts), 34% reported routinely avoiding tick infested areas, and 11% reported routine use of tick repellents (7).…”
mentioning
confidence: 99%
“…There is a gap in the literature on understanding the human and environment relationship and how people perceive their risk of contracting a tick-borne disease such as HME. Related studies that have been done to investigate this human-environment relationship have done so with mosquitoborne diseases (Butterworth et al 2010) and Lyme disease in the endemic region of that tick-borne disease (Gould et al 2008;Herrington 2004;Herrington et al 1997). There have been few or no studies done to investigate the relationship between people and their environment that consider the perceived risks of HME.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, awareness oftickborne diseases and self perceived risks, knowledge and use of preventative practices, and health information from health departments all playa key role in assessing the potential risks of contracting vector-borne diseases (Herrington et al 1997;Herrington 2004;Butterworth et al 2010). With more individuals participating in outdoor occupational or leisure activities that may place them at risk of coming in contact with ticks, a focus on the people's awareness and perceived threats and seriousness of tick diseases may shed light on these components.…”
Section: Statement Of Purposementioning
confidence: 99%
See 2 more Smart Citations